INPATIENT CARE UTILIZATION AFTER JKN: A STUDY CASE IN EAST NUSA TENGGARA - Rahvy, Aisyah Putri; Gani, Ascobat (Universitas Airlangga, 2024)
Background: Healthcare utilization is a predictor of health status among the population. The issues of its accessibility and equity have been raised, particularly after the government launched JKN (Jaminan Kesehatan Nasional) Aim: This study aims to analyze the determinants of inpatient care utilization in East Nusa Tenggara. Method: We used SUSENAS 2019 dataset and carried out descriptive and econometrics analysis to covariates including age, gender, educational level, type of health insurance, employment status, and type of residence. Result: We found that all covariates analyzed were statistically significant in affecting the probability of inpatient care utilization (p-value<0.005). Different patterns of sociodemographic factors among people in East Nusa Tenggara will affect their rate of inpatient care utilization. Conclusion: Inpatient care utilization rate is crucial to measure health accessibility and prevent any aggravated morbidity due to delayed treatment. Strategies to increase inpatient care utilization are needed to provide accessible treatment for all and increasing population health status. Keywords: East Nusa Tenggara, health utilization, hospitalization, inpatient care